Discovery of a natural product-like iNOS inhibitor by molecular docking with potential neuroprotective effects in vivo. - Hai-Jing Zhong; Li-Juan Liu; Cheong-Meng Chong; Lihua Lu; Modi Wang; Daniel Shiu-Hin Chan; Philip Wai Hong Chan; Simon Ming-Yuen Lee; Dik-Lung Ma; Chung-Hang Leung (PLoS ONE)
In this study, we applied structure-based virtual screening techniques to identify natural product or natural product-like inhibitors of iNOS. The iNOS inhibitory activity of the hit compounds was characterized using cellular assays and an in vivo zebrafish larvae model. The natural product-like compound 1 inhibited NO production in LPS-stimulated Raw264.7 macrophages, without exerting cytotoxic effects on the cells. Significantly, compound 1 was able to reverse MPTP-induced locomotion deficiency and neurotoxicity in an in vivo zebrafish larval model. Hence, compound 1 could be considered as a scaffold for the further development of iNOS inhibitors for potential anti-inflammatory or anti-neurodegenerative applications.